2018
DOI: 10.1111/dar.12818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute exercise on drug craving, self‐esteem, mood and affect in adults with poly‐substance dependence: Feasibility and preliminary findings

Abstract: Football, circuit training and walking are feasible therapeutic activities for inpatients with poly-substance dependence. Controlled trials are needed to determine the long-term effects of these activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
1
17
1
1
Order By: Relevance
“…Second, drug craving was assessed using a single-item visual analog scale (VAS) ranging from 0 (no craving for drugs) to 10 (strong craving for drugs). Participants were instructed to indicate how strong their craving for drugs felt “at this moment.” The instrument has been used in previous studies of acute exercise [ 41 ] and it was tested in our recent pilot study [ 36 ], where it was shown to be sensitive to change.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, drug craving was assessed using a single-item visual analog scale (VAS) ranging from 0 (no craving for drugs) to 10 (strong craving for drugs). Participants were instructed to indicate how strong their craving for drugs felt “at this moment.” The instrument has been used in previous studies of acute exercise [ 41 ] and it was tested in our recent pilot study [ 36 ], where it was shown to be sensitive to change.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical power was estimated using G*Power (version 3.1.9.7; Heinrich-Heine-Universität Düsseldorf). Parameters were based on results from our feasibility study [ 36 ] and also took into account previous studies demonstrating medium effect sizes for acute exercise on mood states [ 38 , 45 ]. Assuming an effect size of 0.3 and power (β) of .8, with 3 groups and 5 measurement points, we estimate needing at least 21 participants to test our hypotheses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were instructed to indicate how strong their craving for drugs felt "at this moment." The instrument has been used in previous studies of acute exercise [41] and it was tested in our recent pilot study [36], where it was shown to be sensitive to change.…”
Section: Baseline and Follow-up Assessmentsmentioning
confidence: 99%
“…Changes such as reduced metabolic activity in the prefrontal cortex [8] decreased oxygenation [9] and reduced amount of gray matter in the anterior and prefrontal cingulate cortex have already been reported [10]. Physical exercise has been recommended as a treatment alternative capable of promoting positive effects on cognitive performance, cerebral oxygenation level [13], reduced desire for drugs, improved self-esteem and mood [14]. These results reinforce the role of exercise as an adjunct in the treatment of impaired frontal cortex activity and cognitive function in individuals with drug use disorder.…”
Section: Introductionmentioning
confidence: 99%